Implementasi Manajemen Mutu Terpadu Dalam Meningkatkan Kualitas Pendidikan Di SMP Negeri 16 Surabaya - Pratiwi Hernovianus, Intan; Intan Permatasari, Nabella; Andini , Andini (Politeknik Penerbangan Surabaya, 2025)
Integrated Quality Management is a strategic approach used in various sectors, including education. The implementation of Integrated Quality Management at SMP Negeri 16 Surabaya is very important for improving the quality of education. The purpose of this study is to analyse the implementation of integrated quality management in an effort to improve the quality of education and increase the effectiveness and efficiency of the learning process at SMP Negeri 16 Surabaya. This study employs a qualitative, descriptive approach. This method was chosen because it provides a clear and in-depth explanation of the concepts being studied. The subjects of this study are teachers and the school principal. In this study, information regarding the phenomenon under investigation was collected through observation, interviews, and document collection. Subsequently, a thorough and detailed analysis of this information was conducted. The results of this study indicate that: 1) SMP Negeri 16 Surabaya has implemented a quality management system through effective leadership. 2) The implementation of integrated quality management to support the learning process at SMP Negeri 16 Surabaya has been carried out well. 3) SMP Negeri 16 Surabaya has taken adequate steps in implementing integrated quality management to improve the quality of education